Pineal cyst in bipolar patient with normolithiaemia and positive fibromyalgic tender points - Salvatore Marrone, MD; Antonio Alessandro Biancardino, MD; Evier Andrea Giovannini, MD; Federica Paolini, MD; Benedetta Maria Campisi, MD; Jaime Mandelli, MD; Domenico Santangelo, MD; Salvatore Fanara, MD; Giuseppe Vaccaro, MD; Michele Vecchio, MD; Domenico Gerardo Iacopino, MD, PhD; Luigi Basile, MD (Radiology Case Reports)
Pineal cysts are benign, nonneoplastic lesions of the pineal gland, often identified incidentally on MRI scans. Although these cysts are usually asymptomatic, they can occasionally enlarge and compress adjacent structures, leading to neurological complications such as obstructive hydrocephalus and Parinaud's syndrome. The underlying mechanisms of pineal cyst development remain largely unclear, although inflammation - common in rheumatological conditions such as fibromyalgia - and mechanical stress have been suggested as contributing factors. In addition, the incomplete blood-brain barrier of the pineal gland raises the possibility that chronic lithium therapy, commonly used for psychiatric disorders and also known for its hyperplastic effects, could facilitate cysts formation through lithium accumulation and epithelial stimulation.We report the case of a 49-year-old woman with bipolar disorder on long-term lithium treatment who presented with a pineal cyst and clinical symptoms consistent with fibromyalgia. A review of the literature highlights possible links between pineal cyst formation, systemic inflammation associated with rheumatological disorders and prolonged lithium exposure.Although the hyperplastic properties of lithium in glandular tissue are well documented, there is no conclusive evidence directly linking lithium use to the development of pineal cysts in humans. The possibility of cystic growth driven by the pro-inflammatory environment of fibromyalgia remains plausible and warrants further investigation of the complex interactions between lithium therapy, systemic inflammation and pineal cystogenesis, particularly in patients with coexisting rheumatological and psychiatric disorders.